ALLELOPATHIC EFFECT OF COVER CROP EXTRACTS ON GERMINATION AND INITIAL GROWTH OF WEEDS - Camacho, Lucas Orlandi; de Moraes, Pedro Valério Dutra; Russiano, Maira Cristina Schuster; Morgan, Samara Baú; Salvadori, Camila Natacha; Jaskulski, Eliza; Kniess, Yana Kelly; Rossi, Patricia (Seven Editora, 2026)
The intensive use of herbicides has contributed to the selection of resistant weed populations, highlighting the need for alternative weed management strategies. In this context, allelopathy from cover crops may represent a complementary tool for weed suppression. This study aimed to evaluate the allelopathic potential of aqueous extracts from the shoot biomass of brachiaria (Brachiaria ruziziensis), sunn hemp (Crotalaria ochroleuca), and pearl millet (Pennisetum glaucum) on the germination and early development of Italian ryegrass (Lolium multiflorum), wild radish (Raphanus sativus L.), and beggarticks (Bidens pilosa). The experiment was conducted in a completely randomized design, using aqueous extracts at 10% (w/v). Germination percentage and speed, shoot and root length, and fresh and dry biomass accumulation were evaluated. Brachiaria and sunn hemp extracts significantly reduced all evaluated variables for the three weed species. Pearl millet extract showed a less pronounced allelopathic effect, with no significant interference on germination and dry biomass accumulation of wild radish. These results indicate that brachiaria and sunn hemp exhibit high allelopathic potential and may be used as complementary tools for sustainable weed management.